2002
DOI: 10.1056/nejmoa013169
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin-Resistant Group A Streptococci in Schoolchildren in Pittsburgh

Abstract: In January 2001, during a longitudinal study of schoolchildren, we detected the emergence of erythromycin resistance in pharyngeal isolates of group A streptococci. This clonal outbreak also affected the wider community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(144 citation statements)
references
References 32 publications
9
135
0
Order By: Relevance
“…Health education regarding the GAS infections, their sequelatex agglutination method (HiStrep Latex Test Kit, Hi-Media, Mumbai).The latex kit identifies the groups A, B, C, D, F and G of the Lancefield group of Streptococci. Two more throat swabs were studied from the GAS positive students at intervals of 3 months, to classify them as transient (first culture-positive and the subsequent two cultures-negative), recurrent (first two cultures-positive and the third culture-negative) and chronic carriers (all the three cultures positive) [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health education regarding the GAS infections, their sequelatex agglutination method (HiStrep Latex Test Kit, Hi-Media, Mumbai).The latex kit identifies the groups A, B, C, D, F and G of the Lancefield group of Streptococci. Two more throat swabs were studied from the GAS positive students at intervals of 3 months, to classify them as transient (first culture-positive and the subsequent two cultures-negative), recurrent (first two cultures-positive and the third culture-negative) and chronic carriers (all the three cultures positive) [2].…”
Section: Methodsmentioning
confidence: 99%
“…GAS frequently gets colonized in the throats of asymptomatic persons. There are few studies which have described the natural history of the pharyngeal carriage with GAS [2]. A streptococcal carriage has been defined as the recovery of GAS from the nasopharynx or the oropharynx in the absence of any evidence of an acute infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Given the emergence of group A |S-hemolytic streptococci resistance to macrolides (which has never been documented for penicillins), use of off-guideline therapy for GAS pharyngitis risks both exposure to unnecessary broad-spectrum antibiotics and the potential for treatment failure. 2 ' 28 Our analysis has limitations. First, data were extracted from an EHR using ICD-9 codes to identify GAS pharyngitis.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to ␤-lactams, resistance of GAS to macrolide antibiotics was described as early as the late 1950s and has increased markedly worldwide in the last decade. 33 Martin and colleagues 34 reported an outbreak of pharyngitis caused by erythromycin-resistant serotype M6 GAS strains among schoolchildren in Pittsburgh, PA. This event was of particular concern because within a few months the frequency of macrolide-resistant GAS increased rapidly, and drug-resistant strains spread widely to surrounding communities.…”
Section: Insight Into the Emergence Of Drug-resistant Gas Strains: Anmentioning
confidence: 99%
“…Molecular studies implicated serotype M6 strains of a single clone, and drug resistance was due to the presence of the mefA gene encoding a macrolide efflux pump. 34 Inasmuch as serotype M6 strains are one of the more common causes of pharyngitis and invasive infections 4,19 -21,26,35 and there was considerable conflicting information in the literature about the molecular mechanism of acquisition and transfer of the mefA gene in GAS, we chose to sequence the genome of a genetically representative strain. 26,36 Interestingly, we found that the mefA gene in the Pittsburgh clone was encoded by an unusual 58.8-kb foreign genetic element with characteristics of both a transposon and a prophage.…”
Section: Insight Into the Emergence Of Drug-resistant Gas Strains: Anmentioning
confidence: 99%